Effect of public health nurses’ educational intervention on self-care of the patients with type 2 diabetes - Zandiyeh, Zahra (J Educ Health Promot, 2015)
BACKGROUND: Diabetes is the most common metabolic disease and the sixth cause of mortality in the world. Most of the conducted studies show that the only way to control this disease and prevent its disabling complications is constant administration of self-care. AIM: This study was conducted with the goal of determining the effect of public health nurses’ educational intervention on the self-care of the patients with type 2 diabetes who referred to Hazrat Ali clinic in Isfahan. MATERIALS AND METHODS: This is a two-group two-step clinical trial with a before–after intervention design in which 50 patients with type 2 diabetes and with a mean age of 40–70 years were selected and assigned to study (n = 25) and control (n = 25) groups by allotting them even and add numbers. Educational intervention was conducted in the study group through seven educational sessions. Mean scores of self-care before and after interventions were compared by Toobert and Glasgow brief self-care activities questionnaire. RESULTS: Results showed no significant difference in the self-care scores before intervention in the two groups (P = 0.67, z = 0.43), but the mean score of self-care showed a significant increase after intervention in the study group, compared to the control group (P = 0.002, z = 3.14). CONCLUSION: Based on the obtained results, it is suggested to provide constant education of self-care for diabetic patients in health care centers, with more emphasis on a change in self-care skills and behavior.